Aktivitas Achyranthes Aspera Linn. dalam Menurunkan Kadar Kolesterol dan Glukosa Darah Hewan Uji Resistensi Insulin - Daniek Viviandhari; Maharadingga Maharadingga; Farah Zahria; Putri Hardiyanti (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
The most common causative factor in patients with type 2 diabetes is insulin resistance. Achyranthes Aspera Linn. is known as a medicinal plant which has been shown based on previous research to reduce total cholesterol, triglyceride, and blood glucose levels, but the effective dose is not yet known in insulin resistance rats. Further study is necessary to ensure the effect and also the dose. The purpose of the research was to determine the activity of the extract in reducing levels of total cholesterol, triglycerides, blood glucose, and OGTT in insulin resistance rats. 7 groups (each group consist of 4 animals) were divided, i.e. normal control (not induced), negative group (given with Na-CMC 0.5%), positive group 1 (fenofibrate), positive group 2 (metformin HCl), extract group dose 250, 500, and 750 mg / kg BW for 14 days of treatment. Induction of insulin resistance using streptozotocin. Total cholesterol, triglyceride, blood glucose, and OGTT levels were measured using a clinical spectrophotometer. Oneway ANOVA followed by the Tukey test were used to analyze the data. Data indicated that the third dose extract (750 mg/kg BW) could lower total cholesterol, triglycerides, blood glucose, and OGTT with the percentages of reduction of 48.83%, 48.95%, and 61.31%, respectively, and at OGTT the smallest AUC value was 23,991 mg/dL per minute.